Students’ Perception on the Workbook Used in English Proficiency Class - Silfi Ramadhini Putri; Ririn Ovilia (Universitas Negeri Padang, 2023)
A workbook is one of the most desirable instructional items that can help learners quickly grasp their lessons in a certain subject on their own. A student workbook is an educational tool that includes components that help students learn and ensure knowledge and ability in accordance with the goals outlined in teaching plans. Yet, the workbook used needs some aspect to be maintained or improved according to students view. This descriptive-quantitative research was conducted to five indicator of the workbook based on Cunningsworth criteria of a proper book; approach, skills, topics, practical consideration and organization. The sample was 121 students from both education and non-education program of English Department. These samples were asked about their opinion towards the workbook used in EP class and then they were given questionnaire adapting 28 statements on the perception indicators of the workbook. The collected data were analysed by using descriptive statistical calculation. It was found that the students have positive perception from those indicators of their workbook used in EP class.